KEBIJAKAN FISKAL, MONETER, DAN STRUKTUR DISTRIBUSI KEKUASAAN DAN EKONOMI PADA RUANG - Sumanti; Fitria Nilda; Syatria Hasni; Yustina; Elmasi Tri Oktaviani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia's membership in BRICS reflects an effort to expand economic cooperation amid the transition toward a more multipolar global economic order. This article examines the prospects and challenges of Indonesia's BRICS membership for the national economy. The study employs a qualitative approach through a literature review of scholarly works on BRICS, the Global South, international political economy, and global trade. The findings indicate that BRICS may enhance market access, investment opportunities, and Indonesia's bargaining position in global economic governance. However, challenges remain, including geopolitical dynamics, economic competition among member states, and the need to strengthen domestic competitiveness. The benefits of BRICS membership will largely depend on Indonesia's ability to adapt its economic policies and improve national capacity in a changing international economic environment.